Penerapan Cooperative Learning untuk Meningkatkan Keterampilan Bernyanyi Unisono: Studi di SMP Negeri 1 Dau - Rahmawan, Tegar Punanda; Dyah Pratamawati, Endang Wara Suprihatin; Gusanti, Yurina (Jurnal Pendidikan dan Penciptaan Seni, 2025)
The jigsaw cooperative learning model is  student-centered learning model which the students collaborate with each other in a study group. In the previous unisono singing lessons, teachers applied an inquiry model where students could not collaborate with each other between groups, so that students could not master the material of condicing techniques and sing at the same time. There is a factor in low achievement of the psychomotor aspect of unisono singing material. The purpose of this study is improve the singing skills of unisono in VII B, which obtained KKTP 60 under the school KKTP which is 75 with a graduation percentage of VII B of 60%. The research method is use spiral-shaped Kurt Lewin model Class Action Research with two cycles. The results of the study showed that in the first cycle, VII B obtained percentage completeness in the assessment of 82%. In cycle II, class VII B obtained an increase in the percentage of completeness from 82% to 100%. Can be concluded the jigsaw-type cooperative learning model successful in increasing value of unisono singing skills of students in VII B SMP Negeri 1 Dau.